Vers une ethnographie paysagère ? - Hugo Gassin (Projets de Paysage)
In the course of an ethnographic study of an urban landscape planning project in the Basque Country I observed that the landscape architects in charge of the project at times used the same methods of investigation as I did. The literature also shows that anthropological methods are used in other landscape projects. At the same time, some anthropologists use tools similar to those used by landscape architects to get a better understanding of the representations or sensitive dimensions of the landscape. These observations have led me to establish a parallel between anthropology and landscape architecture via the methods used by landscape architects when studying landscapes. This hypothesis is considered as the legacy of a specific notion within which the landscape is defined as a perceived element. My study shows that in France this system is embodied in various texts that provide a framework for action in the field of landscape architecture, notably from the 1990s onwards with the Loi Paysage. On the occasion of the law’s thirtieth anniversary, this article looks at one of its legacies in research and urban planning, paving the way for the development of an ethnographic approach to the landscape.